GETTING AROUND THE CHALLENGES OF LEARNING ACCOUNTING EDUCATION DURING THE COVID-19 PANDEMIC - Hermawan , Atang (Sean Institute, 2023)
This study aims to analyze the challenges faced by students in studying accounting during the Covid-19 pandemic and find solutions to overcome them. This research was conducted using qualitative and quantitative approaches through data collection through interviews, questionnaires and observation. The results of the study show that the Covid-19 pandemic has presented many challenges to the accounting learning process, including problems with unstable internet access, difficulties in adapting to online learning, and increased anxiety related to health and finances. Based on these findings, several solutions have been proposed, including increasing internet access, using different learning methods, and counseling support and financial assistance for students in need. This research is expected to contribute to the development of more effective learning strategies during the Covid-19 pandemic, particularly in the accounting discipline.